Methodological aspects of quality assurance and modern management in education in Uzbekistan - Ortikov, Eldor; Kurbanova, D; Avazova, Ozoda (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The new conditions that have emerged in Uzbekistan with the beginning of a new phase of reforms have changed the structure of higher education, the demand for their knowledge and skills. Now there is a high demand for personnel who can apply new knowledge in practice, understand the scope of innovative opportunities in a particular profession. These should be highly qualified professionals with analytical skills who can not only competently solve current economic and production issues, but also make the right decisions. It has become necessary to strengthen competition, which encourages the development of higher education institutions and the provision ofquality educational services by them. In the process of reforming the education system in Uzbekistan, based on the positive foreign experience, a system of public management of educational institutions is gradually being introduced through the establishment of guardians and supervisory boards